Characteristics of glioblastoma long-term survivors. (15th October 2021) - Ali, Tamara; Olubajo, Farouk; Rathi, Nitika; Pal, Piyali; Jenkinson, Michael; Brodbelt, Andrew
Abstract: Aims: Glioblastoma (GBM) is the commonest and most aggressive primary malignant brain tumour in adults. A small number of patients survive for >5 years and are referred to as long-term survivors (LTS). This study aimed to quantify and characterise GBM LTS in a single large UK centre. Method: A retrospective observational cohort study was performed. Patients diagnosed with GBM in a single UK centre between 2000–2011 (inclusive) who survived >5 years from diagnosis were included. Histopathological samples were re-examined as per the WHO 2016 classification criteria and tested for molecular biomarkers including MGMT promoter methylation, IDH1/2 mutations, 1p19q codeletion and ATRX. Demographic, imaging, treatment and outcome data were collected. Results: 1130 patients diagnosed with GBM were identified, 30 of whom survived for >5 years. Twenty-three were re-confirmed as GBM histologically and seven were reclassified as anaplastic oligodendroglioma or anaplastic astroctyoma. Median overall survival for this cohort was 6.2 years. We report a 2% 5-year survival, and a 0.7% 7-year survival. LTS-associated factors were younger age (<65 years old), frontal unilateral tumours, maximal management (surgery and chemoradiotherapy), good post-operative performance status (WHO <2), MGMT promoter methylation and IDH1/2 mutation. Conclusion: A small subset of GBM patients survive for >5 years. Most still succumb to the disease, implying 5-year survival is not indicative of a cure. On applying current molecular markers, a quarter of previously diagnosed glioblastoma in this LTS population were revised to be WHO grade III gliomas.